Factors Affecting The Accuracy Of Pre-tender Cost Estimates In The Gaza Strip - Enshassi, Adnan; Mohamed, Sherif; Hadi, Munther Abdel (Penerbit Universiti Sains Malaysia, 2013)
Pre-tender cost estimates of construction projects require extensive knowledge and expertise. The aim of this paper is to identify, evaluate and rank essential factors affecting the accuracy of pre-tender cost estimating from the perspective of clients and consultants. A survey questionnaire was conducted to elicit professionals' views on and experiences with factors affecting the accuracy of pre-tender cost estimates; a total of 70 organisations (i.e., 46 clients and 24 consultants operating in the Gaza Strip, Palestine) responded to the survey. The results of analysing a total of 64 factors considered in the questionnaire reveal that the top five factors affecting the accuracy of pre-tender cost estimating are (1) materials (prices/availability/supply/quality/imports), (2) closure and blockade of borders, (3) project team's experience in the construction type, (4) the experience and skill level of the consultant and (5) clear and detailed drawings and specifications. Kendall's coefficient of concordance was used as a measure of agreement between the two groups of respondents (i.e., clients and consultants) who ranked various factors and it appears that they are generally in agreement. Both clients and consultant groups should focus on the main factors identified in this study to develop effective strategies for accurate cost estimating, which would ultimately lead to successful projects.